A synthetic covalent ligand of the C/EBPβ transactivation domain inhibits acute myeloid leukemia cells. (1st April 2022) - Abdel Ghani, Luca; Yusenko, Maria V.; Frank, Daria; Moorthy, Ramkumar; Widen, John C.; Dörner, Wolfgang; Khandanpour, Cyrus; Harki, Daniel A.; Klempnauer, Karl-Heinz
Abstract: C/EBPβ has recently emerged as a pro-leukemogenic transcription factor that cooperates with oncoprotein MYB to maintain proliferation and differentiation block of AML cells, making C/EBPβ an interesting drug target for AML. Here we have studied the inhibitory potential and biological effects of a synthetic analog of the natural product helenalin, a known inhibitor of C/EBPβ. The synthetic compound inhibits C/EBPβ by covalent binding to cysteine residues in the transactivation domain, thereby causing up-regulation of differentiation-associated genes, cell death and reduced self-renewal potential of AML cells. Suppression of these effects by ectopic expression of C/EBPβ or MYB and gene expression profiling validate C/EBPβ as a relevant target of the helenalin-mimic and highlight its role as a pro-leukemogenic factor. Overall, our work demonstrates that the synthetic helenalin mimic acts as a covalent inhibitor of C/EBPβ and identifies the cysteine residues in the transactivation domain of C/EBPβ as ligandable sites. The helenalin mimic can be considered a potential "lead molecule" but needs further development towards more effective C/EBPβ inhibitors before being used as a therapeutic agent. Highlights: A synthetic helenalin mimic acts as covalent inhibitor of transcription factor C/EBPβ A helenalin mimic abates AML cell proliferation in C/EBPβ- and MYB-dependent manner C/EBPβ supports MYB transcriptional and oncogenic activity in MYB-addicted AML cells C/EBPβ and MYB constitute a druggable pro-oncogenic transcriptional module in AML The mimic is a "lead molecule" that needs further development before its therapeutic use